Strategi Guru dalam Menangani Masalah Kesulitan Membaca Siswa Kelas Tinggi di SDN 2 Padi - Suko Wahono, Muhadi; Isvandiana Purnamasari, Mega; Burhanuddin, Afid (Scholarly Journal of Elementary School, 2025)
Abstract This study aims to: 1) Determine the form of reading difficulties in high grade students at SDN 2 Padi; 2) Knowing the teacher's strategy in dealing with the problem of reading difficulties in high grade students at SDN 2 Padi. This study uses qualitative research. The subjects of the study are teachers of grades IV, V, and VI. The data collection method was obtained from observation, interviews, and documentation. The validity of the data in this study uses triangulation techniques. The data analysis techniques in this study are data reduction, data presentation, and data verification. The results of the study showed that there were still 6 students in the upper class who had difficulty reading. The difficulties experienced by students include a lack of recognition of letters such as diphthongs, digraphs and consonants. The factors that cause the problem are internal factors and external factors. Teachers use learning strategies and provide assistance to students and provide additional hours, then teachers also use additional media such as picture books and audio-visual media.